Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Orangtua Dalam Penanganan Awal Kegawatdaruratan Kejang Demam Pada Balita - Marsia Marsia; Erni Juniartati; Dwi Sulistyawati (Jurnal Ners, 2025)
not subside quickly. This is usually due to a lack of knowledge about the initial handling of febrile seizures in children. This study aims to determine the effect of health education about febrile seizures on parents' knowledge in handling emergency situations in children. This research uses a quantitative method with a quasi-experimental design, employing a Pre and Post Test Without Control Group Design. The study population consisted of parents with children who experienced febrile seizures, with a sample of 33 people selected through consecutive sampling. The study was conducted in the working area of Singkawang Utara 1 Health Center. Data were collected using questionnaires and analyzed using the Wilcoxon Sign Rank Test. The statistical analysis results showed a significance value of 0.000 (p value < 0.05), indicating that health education has an effect on parents' knowledge in handling emergency situations of febrile seizures in children. Health education has been proven to increase parents' knowledge, thus improving the initial handling of emergency situations of febrile seizures in children.